Karakteristik DAS dan Prediksi Debitnya Menggunakan Hidrograf Satuan Sintetik Gama 1 di DAS Klawoguk, Kota Sorong (Watershed Characteristic and Discharge Prediction Using Gama 1 Synthetic Unit Hydrograph in Klawoguk Watershed, Sorong City) - Anif Farida; Achmad Rusdi (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2024)
A unit hydrograph is a direct flow hydrograph obtained from effective rainfall that occurs at a fixed intensity per unit time, is evenly distributed throughout the watershed, and is applied to river basins without automatic water level recorder. The Klawoguk River Basin in Sorong City does not have an automatic water level recorder device (AWLR), with the problem of flooding when it rains with a quite high intensity. The research aims to understand the characteristics of the Klawoguk watershed and estimate the amount of discharge using the HSS Gama 1 method.  The study uses ArcGIS 10.8 to calculate the watershed's characteristics and applies the HSS Gama 1 method to analyse discharge. The research results show that Sub-watershed 1 has the largest area (9,74 km2), which means it can store large amounts of rainwater. The longest main river is Sub-watershed 5 (8.22 km), and the shortest is Sub-watershed 4 (4.95 km). This indicates that Sub-watershed 5 has a longer concentration time, so the risk of flooding is also low. The slope of the main river in the Klawoguk watershed is quite low (0.002-0.023), which indicates potential flooding. The watershed's shape ranges from 0.028 to 0.041, indicating it is not round. HSS Gama 1 analysis shows that the highest peak discharge (Qp) in Sub-watershed 1 at 1.427 m3/sec and the lowest in Sub-watershed 5 at 0.488 m3/sec. The result of this study is expected to provide an overview of discharge conditions based on the physical characteristics of the watershed.